Terminological mapping in the domain of the obstetric radiology: a statistical study based on ontologies - Igor Soares Amorim; Eduardo Beckhauser; Vinícius Andreóli Petrolini; Alexandre Savaris; Aldo von Wangenheim (Instituto de Comunicação e Informação Científica e Tecnológica em Saúde (Icict) da Fundação Oswaldo Cruz (Fiocruz), 2018)
This article bases on a study in which terms of the obstetric radiology domain were collected and arranged, and then we identified whether they are comprised in four distinct controlled vocabularies: OntoNeo, RadLex, LOINC and SNOMED. We present the STT/SC - Sistema Integrado Catarinense de Telemedicina e Telessaúde (Santa Catarina's integrated system of telemedicine and telehealth) and the project of structuring diagnostic reports of tests in obstetric radiology, as well as the theoretical context of information science about controlled vocabulary. We carried out a survey of the terms jointly an expert and a documentary research to the statistical survey of the terms from controlled vocabularies. A hierarchy of the terms collected was established and the coverage of each of the controlled vocabularies in relation to the terms was verified. The SNOMED is the controlled vocabulary with greater potential of use for the indexation of diagnostic reports in the field of obstetric radiology.